2009
DOI: 10.1002/erv.907
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes, body image disturbance and disordered eating amongst adolescents and young adults: A review

Abstract: Considering the role of parents could help improve public health management. Futher exploration of the way adolescents and young adults interpret and perceive parental attitudes and of potential protective factors is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
129
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(154 citation statements)
references
References 76 publications
(113 reference statements)
10
129
0
15
Order By: Relevance
“…Our research support the results of studies showing that parents have a significant influence on the development of their children's body image, body image disturbances and disordered eating [24][25][26]. Associations between several variables describing the socioeconomic situation of a family and the children's eating attitudes proved to be significant.…”
Section: Discussionsupporting
confidence: 88%
“…Our research support the results of studies showing that parents have a significant influence on the development of their children's body image, body image disturbances and disordered eating [24][25][26]. Associations between several variables describing the socioeconomic situation of a family and the children's eating attitudes proved to be significant.…”
Section: Discussionsupporting
confidence: 88%
“…Thirdly, we only included mothers in this study. It is important for future research to also consider fathers, as they too play a significant role in the development of their children's body image (Rodgers & Chabrol, 2009). Indeed, some studies have reported that engaging fathers in body image and Running head: MOTHER DAUGHTER PREFERENCES FOR INTERVENTIONS 11 eating disorder prevention interventions has proven more difficult than involving mothers (Trost, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers play a key role in influencing their daughter's body image (Rodgers & Chabrol, 2009). They can foster positive body image among their daughters by modelling positive attitudes and behaviours towards their own appearance (Abraczinskas, Fisak, & Barnes, 2012).…”
mentioning
confidence: 99%
“…But studies on young adult women suggest it would be only psychological control by the father, whereas psychological control by the mother would have an indirect influence through mediating mechanisms such as maladaptive perfectionism (Soenens et al, 2008) or moderating the relationship between body dissatisfaction and disordered eating (Sira & White, 2010). Thus, an important avenue for future research is to further explore these parental influences as well as daughters' mediating/ moderating mechanisms such as body dissatisfaction, internalization of appearance ideals, appearance anxiety and personality traits (Rodgers & Chabrol, 2009;Soenens et al, 2008;Tetley, Moghaddam, Dawson, & Rennoldson, 2014). Furthermore, recent review papers share a common idea that there are no particular patterns in family functioning associated with eating disorders; rather, family functioning is diverse (Holtom-Viesel & Allan, 2014;Konstantellou, Campbell, & Eisler, 2012;Le Grange, Lock, Loeb, & Nicholls, 2010).…”
Section: Discussionmentioning
confidence: 99%